Crescimento de Qualea dinizii Ducke em floresta natural no bioma amazônico - Cruz, Evanil Almeida (2024)
Knowledge about the growth of native trees individually or in groups is essential for defining actions regarding the use, maintenance and conservation of forest species, as well as guaranteeing their availability for present and future generations. The aim was to morphologically and anatomically describe the tree species Qualea Dinizii Ducke and its natural growth pattern in the northwestern Amazon region of Mato Grosso. In the field, for the descriptive stage and characterization of the species, vegetative and woody material was collected, as well as morphological data from the trunk for morphological characterization and the anatomical structure of the wood to confirm the study species. The dendrometric variables (CAP, Dap, Ht) and stump height (0.15 m) were measured for each tree. The slices were taken in cross-sectional cuts along the stem, at the heights defined for each tree, A0: 0.20 m; 6.20 m; 11.40 m; 19.00 m and 30.00 m; A1: 0.20 m; 1.30 m and 20.00 m; A2: 0.20 m; 1.30 m and 18.00 m; A3: 0.20 m; 1.30 m and 15.00 m and A4: 0.20 m; 1.30 m and 25.00 m. The total height (Ht) of each tree was measured with the trees felled, totaling five trees for the study. The research was conducted using the Complete Trunk Analysis - ANATRO methodology. The ages determined by counting the growth rings using ANATRO resulted in 144 years for tree A0, Dap of 70.00 cm; A1 at 79 years, Dap of 23.23 cm; A2 at 74 years, Dap of 24.82 cm; A3 at 47 years, Dap of 25.14 cm and A4 at 96 years and Dap of 38.83 cm. This study confirmed the periodicity of the growth rings for the species, with partial reconstruction of the trees' growth in height and diameter, which provided annual information on the species' growth rate in its natural habitat. The species had a Mean Annual Increment in diameter of 0.47 cm/year or 47 mm/year, with a DBH of 68.00 cm and 144 years. The Chapman-Richards model was applied to represent and describe the natural growth pattern, resulting in the adjusted equations for Ht and DBH for the Q. dinizii species, in natural forests in the Amazon biome, in the northwest region of Mato Grosso. Relevant results on the dynamics of development and growth accumulated over the years for the species in the Brazilian Amazon region, helping as indicators of intervention in the forest and implementation of sustainable forest management in the region.